Pengembangan Media Pembelajaran Matematika Berbasis Autoplay Media Studio 8 - Aprilia, Ririn; Subarinah, Sri; Kurniati, Nani; Amrullah (Journal of Classroom Action Research, 2025)
Abstract: This research aims to develop learning media based on Autoplay Media Studio 8 that is valid, practical and effective. Learning media is very important to use in the learning process, but in reality teachers rarely use learning media. This type of research is research and development using a 4D model (define, design, develop and disseminate). The subjects used were 24 students from class VIII-C and 1 mathematics teacher at SMPN 20 Mataram. The instruments used were learning media based on Autoplay Media Studio 8, questionnaires and post-tests for students. The data analysis technique used is analysis of validity, practicality and effectiveness of learning media. The results of data analysis show that the Autoplay Media Studio 8-based learning media that was developed obtained an average score for media validation of 0.85, material validation of 0.81, and practicality questionnaire validation of 0.84 with very valid criteria. The practicality of the product received a score of 91% with very practical criteria. Meanwhile, the effectiveness of the product through the post-test received an effectiveness score of 87.5% with very effective criteria. So it can be concluded that the development of learning media based on Autoplay Media Studio 8 is valid, practical and effective for use in the learning process. Keywords: Development Research, Autoplay Media Studio 8 Abstrak: Penelitian ini bertujuan untuk mengembangkan media pembelajaran berbasis Autoplay Media Studio 8 yang valid, praktis dan efektif. Media pembelajaran sangat penting digunakan dalam proses pembelajaran namun pada kenyataanya guru jarang menggunakan media pembelajaran. Jenis penelitian ini penelitian dan pengembangan (research and development) menggunakan model 4D (define, design, develop, dan disseminate). Subjek yang digunakan yaitu 24 orang siswa kelas VIII-C dan 1 orang guru matematika SMPN 20 Mataram. Instrumen yang digunakan berupa media pembelajaran berbasis Autoplay Media Studio 8, angket serta post-test untuk siswa. Teknik analisis data yang digunakan yaitu analisis validitas, kepraktisan dan efektifitas media pembelajaran. Hasil analisis data menunjukkan media pembelajaran berbasis Autoplay Media Studio 8 yang dikembangkan memperoleh skor rata-rata validasi media 0,85, validasi materi 0,81, dan validasi angket kepraktisan 0,84 dengan kriteria sangat valid. Kepraktisan produk mendapatkan skor 91% dengan kriteria sangat praktis. Sedangkan keefektifan produk melalui post-test mendapatkan skor keefektifan 87,5% dengan kriteria sangat efektif. Sehingga dapat disimpulkan bahwa pengembangan media pembelajaran berbasis Autoplay Media Studio 8 valid, praktis dan efektif untuk digunakan dalam proses pembelajaran. Kata kunci: Penelitian Pengembangan, Autoplay Media Studio 8